Les écoles catholiques et la construction des « identités scolaires » en Côte d'Ivoire - Éric Lanoue (Les éditions de la Maison des sciences de l'Homme, 2004)
Stating that Catholic schools belonged to one education sector - either public or private - was often at stake for Church and State apparatuses at the time of African independences. This article presents the construction of Catholic schools'identity in the post-colonial Ivory Coast. It shows how political and religious determinants intervene in this building both from Church and State actors' side: from the very independence, Ivorian Catholic schools are regarded as being almost public schools, which is quite original in Western African countries at that time. At the end of the eighties, this specific status has been challenged. Donor agencies and the Ivorian government wanted these schools to become quality private schools in order to limit the uncontrolled development of non clerical private schools. But observing education strategies led by parents seems also necessary to understand how the Christian schools' identity is being built in Ivory Coast.